An Innovate Robotic Endoscope Guidance System for Transnasal Sinus and Skull Base Surgery: Proof of Concept - Friedrich, D. T.; Sommer, F.; Scheithauer, M. O.; Greve, J.; Hoffmann, T. K.; Schuler, P. J. (Journal of Neurological Surgery Part B: Skull Base, 2017)
Objective Advanced transnasal sinus and skull base surgery remains a challenging discipline for head and neck surgeons. Restricted access and space for instrumentation can impede advanced interventions. Thus, we present the combination of an innovative robotic endoscope guidance system and a specific endoscope with adjustable viewing angle to facilitate transnasal surgery in a human cadaver model.Materials and Methods The applicability of the robotic endoscope guidance system with custom foot pedal controller was tested for advanced transnasal surgery on a fresh frozen human cadaver head. Visualization was enabled using a commercially available endoscope with adjustable viewing angle (15–90 degrees).Results Visualization and instrumentation of all paranasal sinuses, including the anterior and middle skull base, were feasible with the presented setup. Controlling the robotic endoscope guidance system was effectively precise, and the adjustable endoscope lens extended the view in the surgical field without the common change of fixed viewing angle endoscopes.Conclusion The combination of a robotic endoscope guidance system and an advanced endoscope with adjustable viewing angle enables bimanual surgery in transnasal interventions of the paranasal sinuses and the anterior skull base in a human cadaver model. The adjustable lens allows for the abandonment of fixed-angle endoscopes, saving time and resources, without reducing the quality of imaging.
Keywords: robotic; surgery; sinus; endoscopic; skull base; FESS; RAS